ADVANCEMENTS IN ROBOTIC SYSTEMS FOR SIGN LANGUAGE REPRESENTATION: A REVIEW - Lamis Ali Hussein; Zaid Saeed Mohammed (Journal Park Publishing, 2023)
When compared to spoken language, sign language offers a rich linguistic medium that is essential for the deaf and hard-of-hearing community. In order to close the communication gap, there is a great need for the development of robotics and robotic hands that are capable of accurately understanding and replicating sign language gestures. In this review paper, academic research and technological advancements are integrated. A variety of robotic system development methods and tools are presented, and used to interpret and create sign language, it also covers the difficulties and potential uses of these systems' technical advancement. Robotic systems can represent sign language in a variety of ways, including humanoid robots, signing avatars, robotic arms, robots that can be remotely viewed, gesture-controlled robots, and custom-built systems. Each has advantages and disadvantages, and the choice is based on the specific use case and requirements. Also, the paper discusses how human-robot interaction improves sign language representation and how robotic systems can help deaf and hard-of-hearing people learn, It shows how they affect learning and life. These systems can be used in research, education, and interactive settings. The comprehensive review of robotic systems for sign language representation will help researchers and practitioners advance inclusive communication technologies.
Keywords: Sign Language, Humanoid Robotic Arm, Android, Robotics, 3D Printing, Communication, Deaf, Disability, Dumb, DeafBlind, Hardware, Mobile app